Victorian Feminism and Catholic Art: the Case of Mrs Jameson - Gilley, Sheridan (Studies in church history, 1992)
Now Church History’, wrote John Henry Newman in 1843, ‘is made up of these three elements—miracles, monkery, Popery’, so that anyone sympathetic to the subject must sympathize with these. Much the same, however, could be said of Christian art. The young Southey on a visit to Madrid stood incredulous before a series of paintings depicting the life of St Francis. ‘I do not remember ever to have been so gready astonished’, he recalled. ‘"Do they really believe all this, Sir?" said I to my companion. "Yes, and a great deal more of the same kind", was. the reply.’ The paradox was that works of genius served the ends of a drivelling superstition, a dilemma resolved in the 1830s by the young Augustus Pugin, who decided that the creation of decent Christian architecture presupposed the profession of Catholic Christianity. The old Protestant hostility to graven images was in part a revulsion from that idolatrous popish veneration of the Virgin and saints which had inspired frescos, statues, and altar-pieces in churches and monasteries throughout Catholic Europe; but what on earth did a modern educated Protestant make of the endless Madonnas, monks, and miracles adorning the buildings which he was expected as a man of cultivation to admire? At the very least, he required a sympathetic instruction in the meaning of the iconography before his eyes, and some guidance about its relation to the rest of what he believed. The great intermediary in this process was Ruskin; but there was at least one odier interpreter of Catholic art celebrated in her day, Mrs Anna Brownell Jameson, whose most popular works, Sacred and Legendary Art, Legends of the Monastic Orders, and Legends of the Madonna, told the Englishman what he could safely think and feel amid the alien aesthetic allurements of Catholicism.